Current Global Developments in Breast Cancer and Management in Ghana - Clegg-Lamptey, J.N.; Vanderpuye, V. (My University, 2013)
Breast cancer is the leading malignancy globally, and one of the leading cancers in Ghana. Global developments in the management of breast cancer have led to better patient management. These include the use of multidisciplinary teams (MDTs) in the formulation of management plans. These teams form the basis for best practice in the management of breast disease, and there are attempts to incorporate them in the management of Breast cancer in the two main treatment centres in Ghana. Others include the concept of patient-centred care, use of protocols and clinical trials. Developments in mammographic screening have not been reproduced in developing countries like Ghana for many reasons. These include the absence of mammographic facilities and the relatively young age of patients. A suggested programme that involves Clinical Breast examination, Breast self examination and opportunistic screening has been recommended. Triple assessment remains the basis for diagnosis. Of the various means of biopsy now possible, methods for taking biopsy of non-palpable lesions need to be developed in Ghana, since more patients now have mammograms with some of them reporting with non-palpable abnormalities There have been advances in treatment: surgery, radiotherapy and chemotherapy. Biological therapy in the treatment of patients with HER2 receptor overexpression is often hindered by the high cost of treatment. Generally, Breast cancer management in Ghana has kept pace with global developments. The young age breast cancer patients in Ghana, sociocultural differences and financial limitations require some modifications in the approach of the management of this condition in our country.